Health portal: an alternative using open source technology - Costa, C.; Aparicio, M.; Figueiredo, J. P. (International Journal of Web Portals, 2012)
The authors’ study proposes a conceptual model for a health portal user-centered using a calendar interface paradigm. The aim of this proposal intends to use an insight of a patient when interacting with the health services. In order to promote a well-known user reality, the authors adapt a calendar paradigm. The users’ type and the interaction with the system are based on a stakeholder analysis. A state of the art analysis was made to several health portals, from which resulted the identification of the main features in order to shape the proposed concept. From these initial studies we propose a conceptual model of a health portal focused on the users’ needs. Its implementation was performed using a Free/Libre Open Source Software (FLOSS), more specifically a content management system (CMS). This study also includes the preliminary results of a survey conducted to a group of users.